A-site and B-site co-doped BaTiO3-based dielectric ceramic and preparation method thereof
By simultaneously introducing other elements to the A and B positions of barium titanate ceramic dielectric material, BaTiO3-based dielectric ceramics doped with A and B positions were prepared, which solved the problems of poor temperature stability and low energy storage efficiency of barium titanate dielectric ceramics, and achieved higher high temperature stability and energy storage performance.
Patent Information
- Application Number
- CN202411860676.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Barium titanate dielectric ceramics have problems such as poor temperature stability and low energy storage efficiency.
By simultaneously introducing other elements to the A and B positions of the barium titanate ceramic dielectric material, a BaTiO3-based dielectric ceramic doped with A and B positions was prepared, with the chemical formula of (Bax1Cax2Sr1-x1-x2)(Ti0.4La0.2Ce0.2Ta0.2)O3. Specific preparation methods include mixing, ball milling, compacting, sintering and cold isostatic pressure treatment.
It improves the high temperature stability and energy storage performance of barium titanate ceramics, and overcomes the shortcomings of poor dielectric performance and low energy storage efficiency.
Smart Images

Figure BDA0005193128120000061 
Figure BDA0005193128120000071 
Figure BDA0005193128120000072
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic dielectric ceramics, and in particular relates to an A- and B-site doped BaTiO3-based dielectric ceramic and a preparation method thereof. Technical Background
[0002] With the rapid development of electronic technology, the requirements for energy storage performance of dielectric ceramics in increasingly harsh application environments are constantly increasing. In this context, barium titanate-based ceramics, as a typical lead-free dielectric ceramic, have attracted much attention due to its advantages such as low cost, environmental protection and excellent dielectric properties. However, barium titanate has disadvantages such as high remnant polarization strength, low breakdown field strength and unstable dielectric properties, resulting in low energy storage density and efficiency.
[0003] Therefore, it is of great significance to explore innovative ways to improve the dielectric properties and energy storage performance of barium titanate dielectric ceramics.
[0004] A large number of studies have shown that the performance of BaTiO3 can be significantly improved by doping it with various cations at the A or B position. The doping of different cations can increase the disorder and complexity within the oxygen octahedron, which helps to improve the energy storage performance and dielectric properties.
[0005] A-site doping and B-site doping. A-site doping elements include rare earth elements such as Dy, Eu, Y, and Pb, Zn, Bi, Ca, Sr, etc.; B-site doping elements include rare earth elements such as Mn, Nb, Mg, La, Ce, etc. Rare earth elements have a certain inhibitory effect on the grain growth of ceramics and improve the dielectric properties to a certain extent.
[0006] CN114315350A discloses a lead-free wide-temperature energy storage ceramic of sodium bismuth titanate-barium zirconate titanate and its preparation method. The molecular formula of the ceramic material is (1-x)Bi 0.51 Na 0.47 TiO 3-x BZ y Ti 1-y O 3-z Sm, wherein x, y, and z represent the molar fractions of barium zirconate titanate, zirconium ions, and samarium ions, respectively; wherein 0.45≤x≤0.55, 0.3≤y≤0.45, and 0≤z≤0.08. The present invention introduces other elements into A and B of the barium titanate ceramic dielectric material to improve its high temperature stability and also improve its energy storage performance. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of current barium titanate dielectric ceramics, such as poor temperature stability of dielectric properties and low energy storage efficiency, and to propose a barium titanate-based A and B-position co-doped dielectric ceramic.
[0008] In order to achieve the purpose of the present invention, the technical solution adopted is:
[0009] A BaTiO3-based dielectric ceramic doped at A and B positions, wherein the chemical molecular formula of the BaTiO3-based dielectric ceramic doped at A and B positions is
[0010] (Ba x1 Ca x2 Sr 1-x1-x2 )(Ti 0.4 La 0.2 Ce 0.2 Ta 0.2 )O3, 0≤x1≤1,0≤x2≤1, and x1+x2≤1.
[0011] A method for preparing A- and B-doped BaTiO3-based dielectric ceramics, comprising:
[0012] BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, Ta2O5 are weighed according to the measured molar ratio, mixed and dried;
[0013] The dried product is compacted and then fired, and the fired product is ground to obtain a sample powder;
[0014] The sample powder is subjected to cold isostatic pressing and then sintered at high temperature in stages to obtain the A and B-doped BaTiO3-based dielectric ceramic.
[0015] In a preferred embodiment of the present invention, the purity of the raw material powders of BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 is ≥99.7% and the particle size is ≤45 μm.
[0016] In a preferred embodiment of the present invention, the mixing is performed by ball milling, the ball milling medium is anhydrous ethanol, the ball milling beads used are ZrO2 beads, wherein the mass of the mixed powder: the mass of the ball milling beads: the mass of the anhydrous ethanol is 2:3:0.4, an omnidirectional planetary ball mill is used, the ball milling speed is ≥200rpm, the ball milling time is ≥12h, the drying temperature is 100-130°C, and the drying time is ≥8h.
[0017] In a preferred embodiment of the present invention, the compaction pressure of the sample powder is ≥40 MPa.
[0018] In a preferred embodiment of the present invention, the sample powder is sintered at a temperature of 1300-1550° C. and the insulation time is 12-48 hours.
[0019] In a preferred embodiment of the present invention, the product is ground by dry grinding, the ball milling beads used are ZrO2 beads, the mass of the powder: the mass of the ball milling beads is 2:3, the ball milling speed is 200-300rpm, and the ball milling time is ≥12h.
[0020] In a preferred embodiment of the present invention, the high temperature staged sintering after cold isostatic pressing has a specific isostatic pressing pressure of ≥120 MPa and a holding time of ≥5 min;
[0021] High-temperature staged sintering is to place the obtained green billet in a high-temperature sintering furnace, and in the first stage, the temperature is increased from room temperature to 1300-1550°C at a heating rate of 1.5-5°C / min, and kept at this temperature for 2-6 hours;
[0022] In the second stage, the temperature is increased to 1650-1750°C at a heating rate of 5-10°C / min and kept at this temperature for 4-8h; then the temperature is cooled to room temperature at a rate of 1.5-5°C / min.
[0023] The beneficial effects of the present invention are:
[0024] The present invention introduces other elements into A and B of the barium titanate ceramic dielectric material to improve its high temperature stability and energy storage performance, thereby overcoming the defects of the existing barium titanate ceramic dielectric material, such as poor temperature stability of dielectric performance and low energy storage efficiency. DETAILED DESCRIPTION
[0025] The following is further described by specific embodiments:
[0026] Example 1
[0027] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0028] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:2:3:4:2:2:2;
[0029] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 12 h;
[0030] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0031] (4) placing the compacted mixture into a magnesium oxide crucible and heating the temperature to 1300°C at a rate of 5°C / min for 12 hours;
[0032] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and then placed in a ball mill at a speed of 200 rpm for 12 h to obtain the desired sample powder;
[0033] (6) The sample powder was cold isostatically pressed at 120 MPa, maintained at the pressure for 5 min, and then placed in a high-temperature sintering furnace and heated to 1300°C at a rate of 2°C / min, maintained at this temperature for 2 h, and then heated to 1650°C at a rate of 5°C / min, maintained at this temperature for 4 h, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 1.
[0034] Example 2
[0035] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0036] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:3:2:4:2:2:2;
[0037] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 12 h;
[0038] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0039] (4) placing the compacted mixture into a magnesium oxide crucible and heating the temperature to 1300°C at a rate of 5°C / min for 12 hours;
[0040] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and then placed in a ball mill at a speed of 200 rpm for 12 h to obtain the desired sample powder;
[0041] (6) The sample powder was cold isostatically pressed at 120 MPa, maintained at pressure for 5 min, and then placed in a high-temperature sintering furnace and heated to 1300°C at a rate of 2°C / min, maintained at this temperature for 2 h, and then heated to 1650°C at a rate of 5°C / min, maintained at this temperature for 4 h, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 2.
[0042] Example 3
[0043] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0044] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:2:3:4:2:2:2;
[0045] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 12 h;
[0046] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0047] (4) placing the compacted mixture into a magnesium oxide crucible and heating the mixture to 1400°C at a rate of 5°C / min for 24 hours;
[0048] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and then placed in a ball mill at a speed of 200 rpm for 12 h to obtain the desired sample powder;
[0049] (6) The sample powder was cold isostatically pressed at 120 MPa, maintained at pressure for 5 minutes, and then placed in a high-temperature sintering furnace and heated to 1300°C at a rate of 2°C / min, maintained at this temperature for 2 hours, and then heated to 1650°C at a rate of 5°C / min, maintained at this temperature for 4 hours, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 3.
[0050] Example 4
[0051] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0052] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:2:3:4:2:2:2;
[0053] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 24 hours;
[0054] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0055] (4) placing the compacted mixture into a magnesium oxide crucible and heating the mixture to 1400°C at a rate of 5°C / min for 24 hours;
[0056] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and placed in a ball mill at a speed of 300 rpm for 24 h to obtain the desired sample powder;
[0057] (6) The sample powder was cold isostatically pressed at 120 MPa, maintained at pressure for 5 min, and then placed in a high-temperature sintering furnace and heated to 1300°C at a rate of 2°C / min, maintained at this temperature for 2 h, and then heated to 1650°C at a rate of 5°C / min, maintained at this temperature for 4 h, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 4.
[0058] Example 5
[0059] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0060] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:2:3:4:2:2:2;
[0061] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 24 hours;
[0062] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0063] (4) placing the compacted mixture into a magnesium oxide crucible and heating the mixture to 1400°C at a rate of 5°C / min for 24 hours;
[0064] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and placed in a ball mill at a speed of 300 rpm for 24 h to obtain the desired sample powder;
[0065] (6) The sample powder was cold isostatically pressed at 160 MPa, maintained at the pressure for 10 min, and then placed in a high-temperature sintering furnace and heated to 1300°C at a rate of 2°C / min, maintained at this temperature for 2 h, and then heated to 1650°C at a rate of 5°C / min, maintained at this temperature for 4 h, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 5.
[0066] Example 6
[0067] A BaTiO3-based dielectric ceramic doped at A and B positions and a preparation method thereof, the specific steps are as follows:
[0068] (1) BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, and Ta2O5 are mixed in a molar ratio of 5:2:3:4:2:2:2;
[0069] (2) Put the prepared powder into a ball mill, add ZrO2 ball milling beads and anhydrous ethanol at a ratio of 2:3:0.4, adjust the speed of the ball mill to 200 rpm, and the ball milling time is 24 hours;
[0070] (3) subjecting the mixture in step (2) to compaction at 40 MPa;
[0071] (4) placing the compacted mixture into a magnesium oxide crucible and heating the mixture to 1400°C at a rate of 5°C / min for 24 hours;
[0072] (5) The sintered product was crushed and mixed with ZrO2 ball milling beads at a mass ratio of 2:3, and placed in a ball mill at a speed of 300 rpm for 24 h to obtain the desired sample powder;
[0073] (6) The sample powder was cold isostatically pressed at 160 MPa, maintained at the pressure for 10 min, and then placed in a high-temperature sintering furnace and heated to 1400°C at a rate of 2°C / min, maintained at this temperature for 4 h, and then heated to 1750°C at a rate of 5°C / min, maintained at this temperature for 6 h, to obtain the A and B-doped BaTiO3-based dielectric ceramic of Example 6.
[0074] Table 1 is a comparison table of important steps in each embodiment
[0075]
[0076]
[0077] Table 2 is a performance test table of each embodiment
[0078] The dielectric constant is tested by an automatic bridge-type tester under the following test conditions: 0.5Vrms, 1KHz±10%, temperature 300°C. The electrostatic capacitance C is measured, and then the dielectric constant and dielectric loss are calculated based on the sample size.
[0079]
[0080] Comparative Example 1
[0081] A comparative example of the ceramic dielectric material of the present invention. The difference between this comparative example and Example 6 is that in step (4), the compacted mixture is placed in a magnesium oxide crucible and heated to 1200° C. at a rate of 5° C. / min and kept warm for 6 hours; the other steps are the same as Example 6.
[0082] The measured dielectric constant is only 1035F / m, and the dielectric loss is 118.
[0083] Comparative Example 2
[0084] Yang Dianlai, Zhang Yingying, Liu Kun, et al. Preparation of Ho by hydrothermal method 3+ / Y 3+ Study on co-doped BaTiO3-based powders and their dielectric properties[J]. Aging and Application of Synthetic Materials, 2021, 50(06):78-80.DOI:10.16584 / j.cnki.issn1671-5381.2021.06.025. The authors used a hydrothermal method to prepare Ho 3+ / Y 3+ Co-doped BaTiO3-based dielectric ceramics, when w(Ho 3+ ):w(Y 3+ )=3:1, it exhibits the highest dielectric constant of 4542F / m.
[0085] Comparative Example 3
[0086] Wang Lingxu, Guo Xiaodong, Zhang Fengqing, et al. Sr2Bi5FeTi5O 21 Study on dielectric properties of ceramics[J]. Rare Metal Materials and Engineering, 2018, 47(S1):415-419. The authors prepared Sr2Bi5FeTi5O by sol-gel method. 21 (SBFTi) ceramics, the dielectric constant of this ceramic increases with increasing temperature, and exhibits a maximum dielectric constant of about 3300F / m when the temperature reaches 500°C.
[0087] Compared with the prior art, the present invention has the following positive effects:
[0088] Compared with the sol-gel method and the hydrothermal method, the preparation method of the present invention does not require complicated equipment and chemical reagents, and only requires mixing, slurrying and sintering. The process is simple, the cost is low, and it is suitable for large-scale industrial production. The dielectric properties of the prepared dielectric ceramics are 1 to 3 times higher than those of the hydrothermal method and the gel method. The dielectric ceramics prepared by the present invention have a higher dielectric constant and lower dielectric loss, which promotes the development of dielectric ceramics.
Claims
1. A BaTiO3-based dielectric ceramic doped at A and B positions, characterized in that: The chemical formula of the BaTiO3-based dielectric ceramic doped at the A and B positions is (Ba x1 Ca x2 Sr 1-x1-x2 )(Ti 0.4 La 0.2 Ce 0.2 Ta 0.2 )O3, 0≤x1≤1,0≤x2≤1, and x1+x2≤1.
2. The method for preparing an A- and B-doped BaTiO3-based dielectric ceramic according to claim 1, characterized in that: include: BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2, Ta2O5 are weighed in molar proportion, mixed and dried; The dried product is compacted and then fired, and the fired product is ground to obtain a sample powder; The sample powder is subjected to cold isostatic pressing and then sintered at high temperature in stages to obtain the A- and B-site doped BaTiO3-based dielectric ceramic.
3. The BaTiO3-based dielectric ceramic doped at A and B positions as claimed in claim 2, characterized in that: The purity of the raw material powders of BaCO3, CaCO3, SrCO3, TiO2, La2O3, CeO2 and Ta2O5 is ≥99.7% and the particle size is ≤45 μm.
4. The BaTiO3-based dielectric ceramic doped at A and B positions as claimed in claim 2, characterized in that: The mixing is carried out by ball milling, the ball milling medium is anhydrous ethanol, the ball milling beads used are ZrO2 beads, wherein the mass of the mixed powder: the mass of the ball milling beads: the mass of the anhydrous ethanol is 2:3:0.4, an omnidirectional planetary ball mill is used, the ball milling speed is ≥200rpm, the ball milling time is ≥12h, the drying temperature is 100-130°C, and the drying time is ≥8h.
5. The A and B-doped BaTiO3-based dielectric ceramic according to claim 2, characterized in that: The compaction pressure of the sample powder is ≥40MPa.
6. The BaTiO3-based dielectric ceramic doped at A and B positions as claimed in claim 2, characterized in that: The sample powder is sintered at a temperature of 1300-1550° C. and held at a temperature for 12-48 hours.
7. The BaTiO3-based dielectric ceramic doped at A and B positions as claimed in claim 2, characterized in that: The product is ground by dry grinding, the ball milling beads used are ZrO2 beads, the mass of the powder: the mass of the ball milling beads is 2:3, the ball milling speed is 200-300rpm, and the ball milling time is ≥12h.
8. The BaTiO3-based dielectric ceramic doped at A and B positions as claimed in claim 2, characterized in that: The high temperature staged sintering after the cold isostatic pressing treatment is carried out, and the specific isostatic pressing pressure is ≥120MPa, and the holding time is ≥5min; High-temperature staged sintering is to place the obtained green billet in a high-temperature sintering furnace, and in the first stage, the temperature is increased from room temperature to 1300-1550°C at a heating rate of 1.5-5°C / min, and kept at this temperature for 2-6 hours; In the second stage, the temperature is raised to 1650-1750°C at a heating rate of 5-10°C / min and kept at that temperature for 4-8h; then the temperature is cooled to room temperature at a rate of 1.5-5°C / min.
Citation Information
Patent Citations
High dielectric Y5V type three-rare earth doping barium titanate ceramics material and preparation thereof
CN101328061A
High-density barium strontium titanate ceramic and preparation method thereof
CN102976748A
Preparation method of barium strontium titanate dielectric temperature stable ceramic capacitor material
CN103214238A
Ultra-wide-temperature high-stability lead-free capacitor ceramic dielectric material and preparation method thereof
CN104086172A
Method for improving performance of barium-titanate-based electrocaloric ceramic refrigeration device
CN105174942A
Cited By
AlTiO3-based high-entropy ceramic as well as preparation method and application thereof
CN120329030A
BaTiO3-based high dielectric ceramic with positive temperature coefficient at low temperature
CN121850641A